2018
DOI: 10.1080/07357907.2018.1439055
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of MicroRNA-107 on Osteosarcoma Malignancy Through Regulation of Wnt/β-catenin Signaling in Vitro

Abstract: We showed that miR-107 expression was decreased in osteosarcoma (OS) tissues and cell lines. miR-107 mimic significantly decreased OS cell proliferation and inhibited invasion and migration of OS cells. Inhibition of miR-107 expression notably promoted proliferation, invasion and migration of OS cells. In addition, miR-107 mimic inhibited EMT biomarkers and significantly increased apoptosis. miR-107 mimic significantly decreased the protein expression of β-catenin, Cyclin D1, and c-Myc, whereas increased GSK-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Therefore, miR-107 acts as a tumor suppressor or oncogene in different types of cancer. The present study demonstrated that miR-107 may function as a tumor suppressor in lung cancer, which corresponds with previous studies (17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, miR-107 acts as a tumor suppressor or oncogene in different types of cancer. The present study demonstrated that miR-107 may function as a tumor suppressor in lung cancer, which corresponds with previous studies (17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, miR-107 promoted the proliferation and invasion of gastric adenocarcinoma cells through large tumor suppressor kinase 2 (18). However, miR-107 inhibited cell proliferation and metastasis in gastric cancer (19) and osteosarcoma (20). Therefore, miR-107 acts as a tumor suppressor or oncogene in different types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Various miRNAs play a significant role in atherogenesis (Quiat & Olson, ). The role of miR‐107 in several cancers as cell proliferative suppressor and apoptotic promoter has been largely investigated (J. Chen et al, ; Yu, Guo, Cao, Xiao, & Wang, ). This study illustrated the regulatory role and mechanism of miR‐107 in coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Wnt/β-catenin signaling pathway was reported to be activated in OS tissues and cells, and aberrant activation may serve a central role in the tumorigenesis, metastasis and chemotherapeutic responses of OS (31,32). Numerous reports have revealed that microRNAs regulate the Wnt signaling pathway in OS (33)(34)(35), indicating that microRNAs may be the upstream molecules involved in FOXN3 signaling.…”
Section: Discussionmentioning
confidence: 99%